SF-YOLO: A Physics-Guided Framework for Ship Detection in Foggy Maritime Scenarios - Zhou Yang; Tujie Wu; Ruoling Deng; Hubo Chu; Haitao Liu (Journal of Marine Science and Engineering, 2026)
Foggy ship detection frequently suffers from image degradation, blurred object contours and a high missed detection rate. Moreover, most existing maritime datasets lack adequate real fog samples. To solve the above problems, in this paper, the Fog-SMD is constructed on the basis of atmospheric scattering principles and fractal theory in combination with a diffusion model to enrich samples covering various fog scenarios. On this basis, we develop an improved SF-YOLO model that takes YOLOv12 as the basic framework. By embedding the shallow–deep adaptive feature fusion module, scattering-guided refinement module and spatial-frequency dual feature attention module, the model can effectively alleviate feature loss resulting from image degradation in foggy environments. Weighted-EIoU loss is introduced to optimize the bounding box regression and reduce the localization deviation of slender ship targets. The experimental results show that SF-YOLO achieves mAP@50 and mAP@50:95 values of 79.3% and 61.6%, respectively, and outperforms mainstream detection algorithms; compared with YOLOv12n, it improves mAP@50:95 from 59.6% to 61.6%, with only a slight increase in parameters from 2.5 M to 2.8 M, providing a new solution for the practical deployment of detection systems and all-weather maritime monitoring in low-visibility foggy scenarios.

An integrated FDEMATEL-ISM and Bayesian network approach for dynamic deduction of electrical safety risks in battery electric ships - Ruoling Zhou; Liu Yang; Ailong Fan; Chengpeng Wan; Lei Wang (Ocean Engineering, 2026)

Corrigendum to “Nitrogen losses trade-offs through layered fertilization to improve nitrogen nutrition status and net economic benefit in wheat-maize rotation system” [Field Crops Res. 312 (2024) 109406] - Changhong Liu; Shengyan Pang; Xiufeng Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Dong Wang (Field Crops Research, 2026)

Organic fertilizer substitution for chemical fertilizer has a stronger effect on soil bacterial specialists than on generalists - Ruoling Zhang; Weidong Xu; Hao Liu; Xiang Long; Jiaqing Zhou; Min Xu; Hui Cao; Feng Wang (Plant and Soil, 2025)

Fire risk assessment of electric ships on inland waterway based on GT-FFTA: A case study of China - Liu Yang; Junzhang Yang; Ailong Fan; Ruoling Zhou; Lei Wang (Ocean Engineering, 2025)

Reapplication of glyphosate mitigate fitness costs for soil bacterial communities - Hao Liu; Cunzhi Zhang; Bo Zhang; Weidong Xu; Ruoling Zhang; Liting Zhang; Yue Li; Heming Han; Hui Cao (Journal of Environmental Management, 2025)

Liquid-solid triboelectric nanogenerator for bubbles real-time detecting - Xianzhang Wang; Yixing He; Jiaqi Shao; Yuan Liu; Liran Ma; Buzhen Su; Ruoling Deng; Mingxin Hou; Ge Chen; Jun Li (Chemical Engineering Journal, 2025)

Nitrogen losses trade-offs through layered fertilization to improve nitrogen nutrition status and net economic benefit in wheat-maize rotation system - Changhong Liu; Shengyan Pang; Xiufeng Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Dong Wang (Field Crops Research, 2024)

Oxidation with potassium ferrate for the one-pot preparation of carboxylated cellulose II nanocrystals - Yunxiao Liu; Xiaolin Li; Yulong Li; Hongze Xu; Ruoling Liu; Yi Zhang; Zhenchao Zhang; Yuan Yuan; Lu Zong; Lijuan Zhou; Jianming Zhang (Carbohydrate Polymers, 2024)

Chromium immobilization and release by pipe scales in drinking water distribution systems: The impact of anions - Ruoling Ni; Xianxian Chu; Ran Liu; Jinlin Shan; Yimei Tian; Weigao Zhao (Science of The Total Environment, 2024)

Synergistic association of long-term ozone exposure and solid fuel use with biomarkers of advanced fibrosis - Xiaoyu Hou; Zhenxing Mao; Xiaoqin Song; Ruiying Li; Wei Liao; Ning Kang; Caiyun Zhang; Xiaotian Liu; Ruoling Chen; Wenqian Huo; Chongjian Wang; Jian Hou (Environmental Science and Pollution Research, 2023)

Association of temperature variability with the risk of initial outpatient visits for allergic rhinitis: a time-series study in Changchun - Man Xu; Pan Ke; Ruoling Chen; Ping Hu; Bing Liu; Jian Hou; Li Ke (Environmental Science and Pollution Research, 2022)

Association of long-term exposure to ambient air pollution with the number of tuberculosis cases notified: a time-series study in Hong Kong - Man Xu; Ping Hu; Ruoling Chen; Bing Liu; Hongying Chen; Jian Hou; Li ke; Jiao Huang; Hairong Ren; Hui Hu (Environmental Science and Pollution Research, 2022)

Residential greenness attenuated associations of long-term exposure to air pollution with biomarkers of advanced fibrosis - Jian Hou; Xiaotian Liu; Tantan Zuo; Runqi Tu; Xiaokang Dong; Ruiying Li; Mingming Pan; Ruoling Chen; Shanshan Yin; Kai Hu; Zhenxing Mao; Wenqian Huo; et al. (Environmental Science and Pollution Research, 2022)

Independent and combined associations of solid-fuel use and smoking with obesity among rural Chinese adults - Mingming Pan; Jianjun Gu; Ruiying Li; Hao Chen; Xiaotian Liu; Runqi Tu; Ruoling Chen; Songcheng Yu; Zhenxing Mao; Wenqian Huo; Jian Hou; Chongjian Wang (Environmental Science and Pollution Research, 2021)